Konstruksi Makna Emosional dan Budaya dalam Novel Lembayung Senja: Analisis Semiotik Roland Barthes - Dewi Rahma Anjani; Aditya Ansor Alsunah; Lina Siti Nurwahidah; Cecep Dudung Julianto (Asosiasi Ide Bahasa Kepri, 2025)
This article examined the construction of emotional and cultural meanings in the novel Lembayung Senja using Roland Barthes’ semiotic approach. A descriptive qualitative method was employed, and data were collected through reading and note-taking techniques to identify signs that constructed meaning within the narrative. The analysis focused on three levels of signification, namely denotation, connotation, and myth, as represented through symbols such as twilight imagery, characters’ gestures, and emotional metaphors. The findings indicated that these signs not only reinforced the narrative atmosphere but also reflected the characters’ inner journeys, experiences of loss, and underlying cultural values. The emotional and cultural meanings constructed in the novel were interconnected and produced multilayered interpretations, which expanded readers’ understanding of the themes developed by the author. The study demonstrated that Roland Barthes’ semiotic approach was effective in revealing implicit meanings in literary texts and could be applied to other literary works for deeper interpretative analysis.